2011
DOI: 10.1055/s-0030-1256174
|View full text |Cite
|
Sign up to set email alerts
|

Images of the terminal ileum are more convincing than cecal images for verifying the extent of colonoscopy

Abstract: Terminal ileum intubation is achievable rapidly and safely in the majority of patients undergoing colonoscopy. Terminal ileum images provide more convincing evidence of complete examination of the colon than cecal images, even when attempts to capture images specifically of the ICV and appendiceal orifice are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Several prior studies have evaluated the utility of TI intubation in a variety of settings, with potential benefits ranging from confirmation of complete colonoscopy to identifying small bowel pathology. [14][15][16][17] However, most such studies were conducted more than 10 years ago and none previously evaluated successful TI intubation in relation to colonoscopy quality measures. Meanwhile, it has been suggested that the process of attempting TI intubation may deflect folds and uncover previously hidden lesions, 18 which might be particularly important given that colonoscopy is less effective at preventing right-sided cancers than those on the left.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have evaluated the utility of TI intubation in a variety of settings, with potential benefits ranging from confirmation of complete colonoscopy to identifying small bowel pathology. [14][15][16][17] However, most such studies were conducted more than 10 years ago and none previously evaluated successful TI intubation in relation to colonoscopy quality measures. Meanwhile, it has been suggested that the process of attempting TI intubation may deflect folds and uncover previously hidden lesions, 18 which might be particularly important given that colonoscopy is less effective at preventing right-sided cancers than those on the left.…”
Section: Discussionmentioning
confidence: 99%
“…49 The reliability of photodocumentation of the caecum in demonstrating completion has been questioned with ileal photodocumentation advocated as more accurate 50. Biopsy of the ileum may additionally be useful in confirming completion but can be technically difficult, comes with extra costs and has some associated risks, so it is not recommended as a standard of practice 51–53…”
Section: The Standardsmentioning
confidence: 99%
“…While admittedly, there is not strong data to demonstrate the accuracy of images of the caecum to definitively document colonoscopy completion, that practice should be encouraged. Pictures of the ileum have been shown to be more definitive,36 however, routine ileal intubation for this purpose is not recommended 37. Explicit documentation examination extant in the postprocedure report should be required.…”
Section: Quality Assurance In Colonoscopymentioning
confidence: 99%